Generating food security in the year 2020: women as producers, gatekeepers, and shock absorbers - Brown, Lynn R.; Feldstein, Hilary Sims; Haddad, Lawrence J.; Peña, Christine; Quisumbing, Agnes R. (International Food Policy Research Institute, 1995)
Meeting world food needs in the year 2020 will depend even more than it does now on the capabilities and resources of women. Women are responsible for generating food security for their families in many developing countries, particularly in Sub-Saharan Africa. Women not only process, purchase, and prepare food, but they also play a significant role in national agricultural production, producing both food and cash crops. Population growth, urbanization, and the limited potential for increasing production through the expansion of cultivated area imply that, for food needs to be met in the future, yields will have to increase. Agricultural research continues to develop new varieties with higher yields and increased tolerance to unfavorable environmental conditions, but an untapped source of productivity gains could lie in addressing gender disparities in agriculture. This brief examines the key roles that women play in maintaining the three pillars of food security--food production, food access, and food utilization--and it looks at how strengthening these pillars through policies that enhance women's abilities and resources provides a solution to meeting world food needs in the year 2020.